Disorganization or Self-Organization : The Emergence of Business Associations in a Transition Economy - Recanatini, Francesca (World Bank, Washington, DC, 2014)
The transition from plan to market provides a rare opportunity for insight into the endogenous development of economic institutions. Economic activities under the Soviet regime were coordinated by a central authority. Soviet coordinating mechanisms were disrupted during the transition period, leading to an increase in firms' transactions costs. Blanchard and Kremer (1997), among others, emphasize the negative impact of this "disorganization" on output behavior at the beginning of the transition. Although their argument is correct, the authors believe that their work and similar analyses stop short of fully characterizing the transition by concentrating only on reform's disruptive effects. The authors start where the earlier work ends, examining the business associations that emerged spontaneously in response to the transition's challenges. They provide empirical evidence that institutions that help coordinate production and trade emerge spontaneously in a widely "disorganized" environment. Using a largely unexplored set of firm-level data, they document the emergence of business associations at the beginning of the transition and provide evidence that these new coordinating institutions mitigated the initial decline in output. Building on the growing literature on complexity and transaction costs, they interpret the emergence of these informal institutions as the firms' rational attempt to coordinate activities in a decentralized economy. In other words, the creation of complex organizations such as associations is the spontaneous result of a natural tendency in every system to create order at the edge of chaos. Business associations are more likely to emerge where there is disorder to provide their members with stability, coordination, and the information needed to improve performance.